Pengaruh Konsumsi Rumah Tangga, Pengeluaran Pemerintah dan Ekspor Terhadap Pertumbuhan Ekonomi di Provinsi Sumatra Utara - Nurul Aisyah Nst; Puti Andiny; Yani Rizal; Safuridar Safuridar (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Economic growth is one of the important indicators used to determine the achievement of development success. This is certainly not far from the role of several sectors such as consumption, government spending, exports and also other sectors. The aim of this research is to determine the influence of household consumption, government spending and exports on economic growth in North Sumatra Province. This research is quantitative research, the data used in this research is secondary data for the period 2009 - 2023. The data collection method in this research is by collecting through documents. And the analysis technique used in this research is Multiple Linear Regression Analysis. The results obtained are based on partial multiple linear regression analysis. Household consumption variables have no influence and are not significant. Government spending has no influence and is not significant. And the number of exports has no influence and is not significant.